Implementasi Konsep “INature” Pada Interior Daycare Center di Surabaya - Ellysa Novia Halim; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
The Daycare design which is based on interaction with nature will answer the problems of daycare facilities and activity programs that does not support the establishment of character and vulnerability of early childhood’s health. The Daycare will be designed based on nature that aims to create learning experiences through interaction with nature to shape characters of the children who can be more caring with having a more fresh and healthy environment for their childhood development. The method used is a design thinking method which is devided into three processes that is inspiration, ideation, and implementation. Inspiration includes site location surveys, interviews with caregivers and parents who have toddlers, making questionnaires, and measuring rooms. Ideation includes programming analysis and schematic design stages. Implementation includes final design stages, 1: 50 presentation mock up, and presentation board. The concept used is